[Dr. Pilar Ramos Jimenez presents a paper on Health consequences of domestic violence] - Jimenez, Pilar Ramos (Animo Repository, 1998)
Behavioral Science faculty Dr. Pilar Ramos Jimenez presented a paper on Health consequences of domestic violence at an international conference of nurses. The conference was a collaborative project of the Commission on Higher Education and the Centers of Excellence for Nursing Education--St. Paul Universities of Tuguegarao, Cagayan and Iloilo City. The conference was held on January 18-21, 1998.